'Still Waiting' for Justice: Migrant Workers' Perspectives on Labour Exploitation in Ireland. (7th November 2019) - Murphy, Clíodhna; Doyle, David M; Murphy, Muiréad
Abstract: Although there is a growing recognition that a labour law approach is well-placed to tackle migrant workers' vulnerability to labour exploitation, empirical studies in this field are few and far between. This article explores how migrant workers subjected to severe and routine exploitation experience the Irish labour law framework in practice. Drawing on interviews with 23 workers, as well as legal and policy analysis, the research shows that those who have endured the 'continuum' between routine and severe labour exploitation have many commonalities in their lived experiences of labour conditions and law. It is argued that the key problems identified by this research—the intertwinement of employment and immigration enforcement; workers' lack of awareness of employment rights; the ineffectiveness of labour inspections; the uncertain impact of undocumented status on employment rights and difficulties with enforcing employment awards—all point to the failure of institutional labour protections for migrant workers in Ireland. By enabling a more nuanced understanding of exploited migrant workers' needs and perspectives, this study contributes to the ongoing debate on how to develop better regulatory and institutional conditions in Ireland and beyond.